Effect of Goat Manure and on Plant Growth Promoting Rhizobacteria (PGPR) Growth and Yield of Sweet Corn (Zea mays saccharata Sturt .) Plants - Krisdayanti Siahaan (PLANTROPICA: Journal of Agricultural Science, 2021)
Sweet corn (Zea mays saccharata Sturt) is a food crop that is great demand by Indonesians because has  sweeter taste than ordinary corn and has shorter harvest time. 2012, sweet corn production was 19,377,030 tons, while in 2013 was 18,506,287 tons and in 2014 reached 18,548,872.00 tons with harvest area 3,786,376.00 ha. This shows the national maize production still not sufficient for market needs. Techniques for improving sweet corn cultivation can be done providing PGPR and goat manure. The role of PGPR in plant growth also assisted by the presenoe of goat manure, where goat manure is organic material that functions as a provider of nutrients and nutrients for PGPR so that the microorganisms in PGPR are able to survive in the environment. Goat manure is type of manure that contains lots of organic compounds. Soil organic matter can help improve soil physical, biological and chemical properties. Goat manure is friendly to the environment, abundant availability can reduce production costs and increase production through improved soil structure. This study used a randomized block design (RBD) consisting of 9 treatment combinations with 3 replications. Growth parameters include plant height, number of leaves, leaf area and plant dry weight. Yield parameters include fresh weight of cob, fresh weight cob without husk, cob length, cob diameter, sugar content and corn yield per hectare. The combination of goat manure 10 ton ha-1+PGPR 5 ml/L can increase 32.70% yield per hectare, namely 13.88 tonnes ha-1 compared to the control treatment which is 9.33 tonnes ha-1.